EFEKTIVITAS KEBIJAKAN PERATURAN DAERAH NOMOR 1 TAHUN 2015 TENTANG TANGGUNG JAWAB SOSIAL PERUSAHAAN DI KABUPATEN TANJUNG JABUNG BARAT TAHUN 2022 - Dzikriansyah, Aditya; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
West Tanjung Jabung Regency Regional Regulation Number 1 of 2015 was created to implement Law Number 40 of 2007 concerning Limited Liability Companies. However, in the implementation of this regional regulation there are still problems in carrying out corporate social responsibility. The aim of this research is to find out what factors cause the effectiveness of Regional Regulation Policy Number 1 of 2015 concerning Corporate Social Responsibility in West Tanjung Jabung Regency to not run optimally. This research is based on the theory of public policy implementation approaches from Donald Van Metter and Carl Van Horn and the effectiveness theory from Budiani. This theory has 6 variables that can be used to measure the success of a policy, then the effectiveness theory has 4 variables that can be used to measure the level of effectiveness of a policy. The research method used is a descriptive method with a qualitative approach. The results of the research show that the effectiveness of Regional Regulation Policy Number 1 of 2015 concerning Management of Corporate Social Responsibility in West Tanjung Jabung Regency has not run optimally, because the Regent's Regulation has not been made in this Regional Regulation, and there is still a lack of responsiveness from policy actors in dealing with problems that occur. on regional regulations, and lack of coordination and communication between policy actors. Suggestion: Relevant governments (West Tanjung Jabung Regency Regional Government, West Tanjung Jabung Regency Regional Secretariat, and West Tanjung Jabung Regency Bappeda) immediately create and ratify Regent Regulations in Regional Regulations, as well as increase responsiveness and communication and coordination of implementing actors involved in the Regulations This region. Keywords: Effectiveness, Policy Implementation, Corporate Social Responsibility, Regional Regulations